Factors Influencing Decision to Donate Zakat Infaq Sodaqoh (ZIS) via Digital Payment in Indonesia: Integrated TPB and TAM Model - Suhail Suhail; Ugi Suharto; Aimatul Yumna (Center of Strategic Studies (PUSKAS) BAZNAS, 2025)
This study aims to analyze predictor for factors influencing decision to donate ZIS via Digital Payment under integration of Theory of Planned Behavior (TPB) and Technology Acceptance Model (TAM) model. The population in this study comprised Muslim people in Indonesia who had made ZIS donations via digital payment. The sampling technique used was purposive sampling-quota sampling with a total sample size of 400 people. The method used in this research was an explanatory survey with a quantitative approach. The data analysis technique employed was Partial Least Squares-Structural Equation Modeling (PLS-SEM). The result indicate that TPB and TAM model influence decision to donate ZIS moderately, spiritual aspect has significant positive influence toward decision to donate ZIS. The research suggest ZIS institutions to enhance their digital payment systems by strengthening security, and improving features and marketing to increase customer satisfaction value and optimize ZIS collection in Indonesia through digital payment.